Prescribing pattern of antibiotics and susceptibility of pathogens in upper respiratory tract infections: a study from a tertiary care hospital - Srikanth, Sashwath; Mohapatra, Satyajit; Tharunya, P.; Rani, R. Jamuna (International Journal of Research in Medical Sciences, 2020)
Background: Upper respiratory tract infections are mostly caused by viruses and are self-limiting. But it is seen that drug therapy is restored to many of them without adequate justifications. Sometimes multiple drug therapy imposes high cost burden on patients. Use of antibiotics in URTI patients have led to rise in bacterial resistance. So, this study was aimed to analyse the prescription pattern in upper respiratory tract infections and the antibiotic susceptibility of the isolated organisms. Methods: An observational cross-sectional study was conducted in a tertiary care hospital for a period of three months. Based on the inclusion and exclusion criteria sixty patients were selected. Prescriptions of these patients were collected and analysed for the various WHO prescription indicators like average number of drugs per encounter, percentage of drugs prescribed by generic names, percentage of drugs prescribed as injection, drugs form the essential drug list etc. The swabs were collected from the site of infections and were analysed for the bacterial growth. Also, the antibiotic susceptibility of these organisms was tested. Results: A total of sixty prescriptions were collected and analysed. The average number of drugs per prescription was 2.21. Antimicrobials were prescribed in 90% of cases. Approximately 50% cases the combination of amoxicillin and clavulanic acid was prescribed. The percentage of drugs prescribed by generic names was 87% and 68% drugs were form the essential drug list. The culture report of the specimen collected from the swabs showed that only 50% of cases were of some bacterial origin. And the organisms isolated were less susceptible to the antibiotics that were prescribed. Conclusions: This study of prescribing patterns in patients gives appropriate feedback and awareness among health care providers. Rationale prescribing practice will prevent antibiotic resistance and reduction in the adverse drug reactions.